2016
DOI: 10.1111/1744-7941.12120
|View full text |Cite
|
Sign up to set email alerts
|

How ethical leadership cultivates healthy guanxi to enhance OCB in China

Abstract: Ethical leadership has been documented as a critical factor influencing employee behavior. This study aims to expand on previous research by investigating how ethical leadership cultivates healthy Chinese guanxi between employees and their supervisors and influences employee organizational citizenship behavior (OCB). We propose that two types of Chinese guanxi, favor‐seeking guanxi and rent‐seeking guanxi, may play a mediating role in the relationship between ethical leadership and OCB. Using survey data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 80 publications
3
17
0
Order By: Relevance
“…28 Increasing empirical evidence has shown that ethical leaders inspire employees to adopt OCBs in the workplace to help supervisors, fellow workers, and customers. 29,30 In nursing, studies have documented that ethical leadership is related to…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…28 Increasing empirical evidence has shown that ethical leaders inspire employees to adopt OCBs in the workplace to help supervisors, fellow workers, and customers. 29,30 In nursing, studies have documented that ethical leadership is related to…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Given that, researchers have made much effort to identify the driving forces of SSG. For example, different leadership styles such as ethical leadership have been well documented as critical factors influencing SSG (Ko et al, 2017).…”
Section: Ssbl and Ssgmentioning
confidence: 99%
“…Human resource (HR) scholars and practitioners acknowledge the need to encourage employees to go above and beyond the call of duty and undertake discretionary activities that are not part of their formal job descriptions (Ko et al. 2017; Motowidlo 2000; Rose 2016; Son and Kim 2016; Werner 2000). Such organizational citizenship behaviors (OCB), or the ‘good soldier syndrome’ (Organ 1988), can enhance employer performance (Lin and Peng 2010) and generate positive outcomes for employees, by fueling their creative performance (He, Gu and Liu 2018) and sense of meaningfulness (Russo, Guo and Baruch 2014), for example.…”
Section: Introductionmentioning
confidence: 99%